Researcher Observational Analysis of the Role of Educational Facilities on Students' Achievement - Nepal, Bijaya; Maharjan, Ramkrishna (Journal of Advanced Academic Research, 2017)
This study was undertaken to analyse the researcher's observation on different five variables: school’s library, e-library, science laboratory, availability of computer laboratory and its management. These educational facilities effect on the learning process and the achievement of the students’. The main objective of this study was to analyse the role of schools' educational facilities on students' achievement on community-based school and institutional schools of Central Development Region of Nepal. The data presented in this paper were collected to know the measurement of availability of educational facilities and students' achievement from the selected schools for the research. This study was conducted from January to July 2014. During this time, observation checklist was designed to obtain descriptive results using cross tabulation and percentage; and multi-stage sampling methods were applied. The sample size was taken proportionately from 3,125 numbers of Secondary and Higher Secondary schools. The selected districts were Sindhupalchok, Kavre, Makwanpur, Kathmandu and Chitwan. From the universe, 32(1.02 percent) schools were taken by using proportionate stratified random sampling. The value of data Cronbach's Alpha is 0.86 within 36 variables. Analysis of data was done by using the SPSS version 20. Chi-square test was applied to analyze the data. There was significance association (p=.000) between community and institutional schools students' achievement test min score of science and computer subjects and significance association (p=.010) among ecological region (Mountain, Hill, Valley and Terai) students achievement test min score of five core subjects has been found which means that the availability and management of educational facilities and achievement in most of the private schools are better than governmental one.